Anatomy and palynology of endemic Stachys iberica Bieb. Subsp. Iberica var. densipilosa Bhattacharjee (Lamiaceae) from Turkey - Erkara, Ismuhan Potoglu; Koyuncu, Onur; Ardic, Murat; Yaylaci, Omer Koray (Bangladesh Journal of Botany, 2011)
Bangladesh J. Bot. 39(2): 131-136, 2010 (December)